The Influence of Information Quality on User Interest in Accessing the ISumenep Reading Application - Fajriyah, Annisa; Hasanah, Hamidatun (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2025)
The ISumenep reading app is a new reading app that provides a digital collection for the people of Sumenep. Despite having a fairly large collection for a new reading app, its visitor access experienced a decline in 2022. This study was conducted to determine whether there is an influence of the quality of information available on user access interest in this app. The research method used was a quantitative method with simple random sampling and a simple linear regression test. The data collection technique involved observation and the distribution of questionnaires to a number of respondents obtained from the usernames or users of the ISumenep reading app. The results of the study showed that there was a positive influence between the information quality variable and the access interest variable, with an influence value of 81%. This indicates that improving the quality of information in the ISumenep reading application will clearly contribute to increasing users' interest in accessing the application itself. This study can serve as a reference for similar institutions planning to develop similar reading applications, particularly in terms of information quality related to format, completeness, relevance to user needs, as well as the accuracy and timeliness of the information provided.